The Effect of Variations of Cese Waste Waste Levels on Marshall Parameters in Ac-Wc Layer - Muhammad Isradi; Imam Sindu Baskoro; Jaewono Prasetijo; Sumiyati (Journal of World Conference (JWC), 2021)
In the asphalt pavement mixture, filler is needed to support the performance of the pavement construction in order to withstand traffic loads. Various types of fillers have been widely used, including rock ash, portland cement and others. However, the limitation of natural resources encourages the use of waste materials in the construction of road pavements, a potential for the production of bagasse. In this study, sugar cane waste was used as a filler in the asphalt pavement mixture. The research method used is an experimental method, where the experiment is carried out to obtain a data set and analysis of test results. The test was carried out in 2 stages, namely testing the test object with Portland cement filler which was carried out to obtain Marshall parameters and KAO values ??and testing of the test object with bagasse ash filler to produce Marshall parameters and optimum filler content values. The results showed that the use of bagasse ash waste with a proportion of 5% to the weight of the filler increased stability. Tests carried out on the AC-WC layer mixture obtained the KAO value of 5.7% and the optimum filler content of 5.5%. The stability value with 7% bagasse ash filler obtained 1237.1 kg by immersing the test object for 30 minutes and 1156.4 kg with 7% bagasse ash filler by soaking the test object for 24 hours at 60 ° C, meeting the minimum requirements of 800 kg.